INTEGRASI PENDEKATAN MULTIDISIPLINER DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Achmad Qusyairi; Dwi Cahyo Utomo; Devia Rizqiyah (Jurnal Manajemen dalam Pendidikan, 2026)
This study aims to analyze the implementation of the multidisciplinary Islamic Religious Education (PAI) learning model at MTs Bustanul Faizin. The study used a qualitative approach with a case study type to gain a deep understanding of the learning implementation process. Data were collected through participatory observation, in-depth interviews, and documentation studies involving the principal, vice principal of curriculum, PAI teachers, and students as informants. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldana, which includes data collection, data condensation, data presentation, and drawing and verifying conclusions. The results of the study indicate that the implementation of the multidisciplinary PAI learning model is realized through three main aspects, namely the integration of PAI materials with various disciplines, the application of a collaborative problem-based learning model, and collaboration between teachers in supporting integrated learning. These three aspects form a more contextual, participatory, and student-centered learning process so that Islamic values ​​can be understood more comprehensively and connected to various life issues. This research provides a conceptual contribution to the development of multidisciplinary Islamic Education learning while offering practical implications for madrasas in designing learning that is more integrative, relevant, and adaptive to the demands of 21st-century education.   Keyword: Multidisciplinary Islamic Education Learning; Madrasah Tsanawiyah; Learning Integration; Collaborative Learning.